CSR in South Africa mining sector - Koloti, Lehlohonolo (2015)
There are distinct ways in which mining companies in South Africa operate today that are different from the operations three decades ago. Companies have grown in proportion, and the extension of the businesses is directly proportional to the mining activities hence the ultimate prize of degradation and related challenges has to be faced. There is increasing need to understand the relationship between corporate social responsibility and company returns. Both the opponents and proponents of CSR argue their case through convincing arguments presented here concerning the subject as brought out in this discussion. The immediate stakeholders of any company are the consumers, and they form a critical component of the company’s operations. A study of the evolution of CSR Mining in South Africa strategies is critical; as brought out in the discussion of CSR strategies employed three decades ago with what is done today